2020
DOI: 10.3390/app10124317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inulin Addition on Properties of Natural Yogurt

Abstract: The influence of the amount of inulin addition (3%, 6%, 9%, 12% or 15% w/w) on the physicochemical properties of natural yogurt was analyzed. The acidity (titration; pH), texture parameters (penetration test), viscosity curves (rotational rheometer), microrheology (macroscopic viscosity index, MVI; elasticity index, EI; solid-liquid balance—SLB; multi-speckle diffusing-wave spectroscopy, MS-DWS) and physical stability (syneresis; LUMiSizer test) of yogurts were investigated. All samples were non-Newtonian pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…This increase contributed to the high metabolism activity of starter cultures with increasing the inulin, which in turn, elevates the acidity development (Akın et al., 2007). However, this was not in agreement with other studies that increasing the inulin in yogurt is decreasing the acidity (Balthazar et al., 2016; Helal et al., 2018; Żbikowska et al., 2020). This can be related to the metabolism activity of starter cultures used to make yogurt.…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…This increase contributed to the high metabolism activity of starter cultures with increasing the inulin, which in turn, elevates the acidity development (Akın et al., 2007). However, this was not in agreement with other studies that increasing the inulin in yogurt is decreasing the acidity (Balthazar et al., 2016; Helal et al., 2018; Żbikowska et al., 2020). This can be related to the metabolism activity of starter cultures used to make yogurt.…”
Section: Resultscontrasting
confidence: 66%
“…Another study found that the overrun and glass transition of yogurt improved with the addition of 4 and 6% inulin while hardness was decreased (Muzammil et al., 2017). Furthermore, the addition of inulin at a range of 3 to 15% improved the functional characteristics with low syneresis (Żbikowska et al., 2020). Additionally, the apparent viscosity of yogurt increased with adding inulin up to 2% to yogurt (Helal et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The physical stability of yoghurts was determined with an analytical centrifuge LUMiSizer 6120-75 (L.U.M. GmbH, Berlin, Germany) by measuring the intensity of transmitted near-infrared light in suspension, and recording of light intensity profiles as a function of time and position of the sample (“fingerprints”) [ 44 , 45 ]. Stability was shown as a space- and time-related transmission profile over the sample length.…”
Section: Methodsmentioning
confidence: 99%
“…The reported values represented the average of six replicates. The data were analyzed by the delivered software (SepView 6.0; LUM, Berlin, Germany) and the instability index was calculated [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Viscosity curves were described by Ostwald s mathematical model τ kγ n , where: τshear stress Pa , k -consistency index mPas , γ -shear rate s 1 , n -dimensionless flow index. Coefficients of variation of viscosity during shearing were computed 33 . Measurements were made three times for each sample.…”
Section: Viscosity Measurement Of Creamsmentioning
confidence: 99%